Reduction of methicillin-resistant Staphylococcus aureus biofilm growth and development using arctic berry extracts - Aguilera-Correa, John Jairo; Nohynek, Liisa; Alakomi, Hanna-Leena; Esteban, Jaime; Oksman-Caldentey, Kirsi-Marja; Puupponen-Pimiä, Riitta; Kinnari, Teemu J.; Perez-Tanoira, Ramon (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Surgical site infection remains a devastating and feared complication of surgery caused mainly by Staphylococcus aureus (S. aureus). More specifically, methicillin-resistant S. aureus (MRSA) infection poses a serious threat to global health. Therefore, developing new antibacterial agents to address drug resistance are urgently needed. Compounds derived from natural berries have shown a strong antimicrobial potential. Methods This study aimed to evaluate the effect of various extracts from two arctic berries, cloudberry (Rubus chamaemorus) and raspberry (Rubus idaeus), on the development of an MRSA biofilm and as treatment on a mature MRSA biofilm. Furthermore, we evaluated the ability of two cloudberry seed-coat fractions, hydrothermal extract and ethanol extract, and the wet-milled hydrothermal extract of a raspberry press cake to inhibit and treat biofilm development in a wound-like medium. To do so, we used a model strain and two clinical strains isolated from infected patients. Results All berry extracts prevented biofilm development of the three MRSA strains, except the raspberry press cake hydrothermal extract, which produced a diminished anti-staphylococcal effect. Discussion The studied arctic berry extracts can be used as a treatment for a mature MRSA biofilm, however some limitations in their use exist.